Penerapan P5 Dengan Tema Hidup Cinta Lingkungan dalam Mengembangkan Karakter dan Peduli Lingkungan pada Siswa Kelas 1 SD Negeri 74 Kota Bengkulu - Dwi Jayanti, Cici; Yurni, Fenti; Andriyani, Rika; Marlistina, Via; Asvio, Nova (Yayasan Darussalam Bengkulu, 2023)
The character of caring for the environment must be taught in elementary schools, one of which is through children's character education lessons. The aim of this research is to form environmentally caring character in elementary school students through children's character education learning. Children's environmentally caring character is not formed by itself but must be stimulated repeatedly. The right way to Developing environmentally caring character is through the habituation method. Indicators of the environmentally caring character of elementary school children are keeping the environment clean, being responsible for the environment, and caring for/preserving the environment. Based on observations made by researchers in class 1 of SDN 74 Kota Bengkulu, children were still found whose environmentally caring character had not yet developed, this was because the habits carried out by the teachers there had not been carried out optimally. The data collection tools used were observation, interviews and documentation methods. With data reduction analysis techniques, data presentation and drawing conclusions. Based on the results of this research, the author can conclude that in the teacher's process of developing children's environmentally caring character through the habituation method there are still habituation steps that have not been carried out by the teacher, namely the teacher still has not reminded children who have forgotten to carry out positive habits in caring for the environment. Therefore, the teacher's process in developing children's environmentally caring character must be carried out through a habituation method that is carried out repeatedly.